1998
DOI: 10.1097/00005392-199805000-00092
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Function, Mental Health and Psychosocial Functioning in 22 Adolescents With Bladder Exstrophy and Epispadias

Abstract: The present multimodal outcome study revealed that adolescents with bladder exstrophy and epispadias had significant physical and mental problems. Genital malformation, and urinary and fecal incontinence may have a negative impact on mental health and psychosocial functioning. Our findings emphasize the need to include psychosocial experts on health care teams to reveal the amount of distress caused by these anomalies and to offer psychosocial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 35 publications
3
48
2
2
Order By: Relevance
“…first smile 2 (1-2); reaching out 3.5 (3-4); sitting without help 7.4 (7-8.6); walking without help 14 (13)(14)(15)(16)(17); and speech development, i.e. first word spoken 10 (9-12.4) and first three-word sentence 19.5 (18)(19)(20)(21)(22). Despite early major surgical interventions and long immobilization after bladder closure, with or without osteotomy, all milestones were reached within the normal range, with no differences between females and males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…first smile 2 (1-2); reaching out 3.5 (3-4); sitting without help 7.4 (7-8.6); walking without help 14 (13)(14)(15)(16)(17); and speech development, i.e. first word spoken 10 (9-12.4) and first three-word sentence 19.5 (18)(19)(20)(21)(22). Despite early major surgical interventions and long immobilization after bladder closure, with or without osteotomy, all milestones were reached within the normal range, with no differences between females and males.…”
Section: Resultsmentioning
confidence: 99%
“…Most publications on quality-of-life outcome in patients with BEEC reflect the results of single-institution experience [3,14,16,[20][21][22]. By contrast, the 122 patients evaluated here received their primary surgical intervention in 32 different hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…1 Additionally, the penis appears in virtually every aspect of life, such as medicine, religion, art and culture, the media and the common folklore. Concerns over penile size and a desire for a longer penis are common in the male population, and the number of male patients seeking andrological consultations for a 'short penis' is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 41-85% of post-pubescent males were satisfied with their genital appearance after surgical reconstruction. [16][17][18] However, a study by Diseth et al 16 demonstrated that whereas 41% of patients were satisfied with their penile appearance, all of the patients demonstrated some level of psychosexual dysfunction or psychiatric disorders including low levels of genital touching and initiating sexual contacts, depression, poor body concept, withdrawal and anxiety. It should be noted, however, that this study was not controlled and the population may be too few to accurately claim this degree of impairment.…”
Section: Exstrophy-epispadias Complexmentioning
confidence: 99%
“…Although nearly 100% of these male patients can achieve normal erections adequate for sexual activity, infertility is problematic. [16][17][18][19] A significant number of these patients do not ejaculate normally. For instance, Stein et al 17 report that none of the 35 patients ejaculate normally following genital reconstruction.…”
Section: Exstrophy-epispadias Complexmentioning
confidence: 99%